2019
DOI: 10.5961/jhes.2019.306
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual, phenomenal, thematic and methodological choices in the sense of higher education of turkey

Abstract: ÖZBu çalışmanın amacı; Türkiye'nin yükseköğretimi alanında, son yıllarda ele alınan çalışmaların betimsel içerik analizinin gerçekleştirilmesidir. Bu araştırmada, Türkiye'nin yükseköğretimi bağlamındaki çalışmaların tematik, olgusal ve kavramsal içerikleri genelleyici bir tarzda ortaya çıkarılmış ve araştırmacıların çalışmalarını yöntembilimsel açıdan, hangi yaklaşımlarla gerçekleştirdikleri araştırılmıştır. Bu sistematik derleme, esasen bir betimsel içerik analizidir ve Türkiye bağlamında yükseköğretim konusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Turkish higher education research was explored within five-year terms. However, all the doctoral studies before 2000 were aggregated as the millennium was found to be the year of momentum for the rapid growth of Turkish higher education research (Soysal et al, 2019). Tight's (2012a) typology of themes was adopted for the construction of the topics or themes in Turkish higher education research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Turkish higher education research was explored within five-year terms. However, all the doctoral studies before 2000 were aggregated as the millennium was found to be the year of momentum for the rapid growth of Turkish higher education research (Soysal et al, 2019). Tight's (2012a) typology of themes was adopted for the construction of the topics or themes in Turkish higher education research.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, academic journals have been more commonly used as data sources by scholars globally (Chen & Hu, 2012;Hutchinson & Lovell, 2004;Jung, 2015;Tight, 2004Tight, , 2007Tight, , 2012bTight, , 2012cTight, , 2013Tight, , 2014Tight, , 2015aRitter, 2012). Both doctoral dissertations and academic journals were also exploited by Turkish scholars (Aydın, Selvitopu & Kaya, 2018;Karadağ, 2018;Kıranlı Güngör & Güngör, 2020;Soysal, Radmard, Kutluca, Ertepınar, Ortaç, Akdemir & Türk, 2019). From a more specific perspective, Şenay,…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants stated that the internationalization and internationalization of universities is effective in the preference of universities. Turkey's higher education should create quality assurance by taking into account international changes, increase human resources in terms of quality and quantity, create a well-defined qualifications framework and provide coordination between institutions, and the internationalization strategy should be evaluated within the scope of these paradigms (Soysal et al, 2019). In recent years, it is one of the most important expectations of the students that universities provide quality in teaching and learning (Maskell & Collins, 2017).…”
Section: Discussionmentioning
confidence: 99%